INVESTIGATION OF SOME PROPERTIES OF ZINC-NICKEL ALLOY PLATING WITH TRIETHANOLAMINE, p-AMINOBENZENESULFONIC ACID, AND GELATINE - Gezerman, Ahmet Ozan (WORLD SCIENTIFIC PUBL CO PTE LTD, 2020)
Anticorrosion requirements for the metallurgy, automotive, and aeronautical industries have increased in recent years, for which alternative plating chemicals must be developed. This study focuses on obtaining a Zn-Ni alloy plating with higher corrosion resistance and brightness. For this purpose, tetraethylenepentaamine as complexing agent, triethanolamine as the surfactant, and gelatin and p-aminobenzenesulfonic acid as brightening agents for the plating were selected and their optimal concentrations were determined for applications. The optimal Zn-Ni ratio and plating thickness were analyzed using an X-ray Dal device. Improved plating performance of the Zn-Ni alloys was achieved with a Zn-Ni alloy containing 12-14% Ni.
Keywords: Zn-Ni alloy; electroplating; corrosion; triethanolamine; tetraethylenepentaamine; diethylene triamine; CORROSION-RESISTANCE; ELECTRODEPOSITED ZN; ALKALINE BATH; COATINGS; FE; MICROSTRUCTURE; DEPOSITION; BEHAVIOR; STEEL; Chemistry; Physics